2018
DOI: 10.4279/pip.100001
|View full text |Cite
|
Sign up to set email alerts
|

Pattern formation mechanisms in sphere-forming diblock copolymer thin films

Abstract: The order-disorder transition of a sphere-forming block copolymer thin film was numerically studied through a Cahn-Hilliard model. Simulations show that the fundamental mechanisms of pattern formation are spinodal decomposition and nucleation and growth. The range of validity of each relaxation process is controlled by the spinodal and order-disorder temperatures. The initial stages of spinodal decomposition are well approximated by a linear analysis of the evolution equation of the system. In the metastable r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 66 publications
(99 reference statements)
1
2
0
Order By: Relevance
“…In this case, the GB is a mirror + glide plane. These SU sequences are very similar to those proposed to describe the structure of tilt GBs in a variety of two- or three-dimensional polycrystalline materials where atoms, molecules or particles are organized in hexagonal lattices through interactions of very different nature, exemplified in semiconductors, 61 graphene, 63–66 bubble rafts 67 magnetic bubble arrays, 56 block copolymer films, 50,51,68 or the cornea of some butterflies. 54…”
Section: Resultssupporting
confidence: 66%
“…In this case, the GB is a mirror + glide plane. These SU sequences are very similar to those proposed to describe the structure of tilt GBs in a variety of two- or three-dimensional polycrystalline materials where atoms, molecules or particles are organized in hexagonal lattices through interactions of very different nature, exemplified in semiconductors, 61 graphene, 63–66 bubble rafts 67 magnetic bubble arrays, 56 block copolymer films, 50,51,68 or the cornea of some butterflies. 54…”
Section: Resultssupporting
confidence: 66%
“…During solvent evaporation, these methods produce highly disordered patterns with limited applications due to the presence of defects and elastic distortions. A number of techniques, including as chemo- and grapho-epitaxy, shear flow, and electric and geometric fields have been employed to produce patterns with well-defined orientational and positional order in block copolymer thin films with different architectures. ,− Due to its simplicity and low cost, solvent annealing techniques are one of the most promising approaches to control long-range order and symmetry of block copolymer patterns. In particular, previously, we found that annealing under supercritical carbon dioxide (scCO 2 ) speeds up the mechanisms of coarsening and stabilizes hexagonal patterns with a degree of order, which is unreachable with conventional thermal annealing techniques. , Considering its low cost, wide availability, moderate critical conditions (critical temperature T C = 31 °C, critical pressure P C = 73.8 bar, and critical density ρ C = 0.468 g/cm 3 ), gas-like diffusivity, and low interfacial tension with the polymers, supercritical carbon dioxide, scCO 2 , is increasingly being used as a green solvent in different fields, including biomedical applications, polymer processing, and polymer synthesis. …”
Section: Introductionmentioning
confidence: 99%
“…As the standard methods employed to produce ordered block copolymer films involve a phase transition from a disordered state, the resulting patterns usually contain nonequilibrium elastic distortions and defects that disrupt the order and prevent their use for many applications. ,,, Although the density of defects can also be reduced by thermal treatments, it has been found that this process is prohibitively slow for most technological purposes. In addition, depending on the chemical architecture of the copolymer, thermal annealing may also result in the degradation of the polymer system. Therefore, a variety of alternative techniques, such as chemo- and grapho-epitaxy, shear flow, electric, or geometric fields have been explored to improve the degree of order in block copolymer thin films with different architectures. ,,, …”
Section: Introductionmentioning
confidence: 99%